If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10p-3=(12+4p)=7
We move all terms to the left:
10p-3-((12+4p))=0
We add all the numbers together, and all the variables
10p-((4p+12))-3=0
We calculate terms in parentheses: -((4p+12)), so:We get rid of parentheses
(4p+12)
We get rid of parentheses
4p+12
Back to the equation:
-(4p+12)
10p-4p-12-3=0
We add all the numbers together, and all the variables
6p-15=0
We move all terms containing p to the left, all other terms to the right
6p=15
p=15/6
p=2+1/2
| 5/x-7=-4 | | 1.3=r/7+0.3 | | 7(x-3)=x+21 | | 9x+6=-3x-30 | | -20y+15=2-6y+11 | | -17+1=-4(x+2) | | 8x/85=87 | | 12u+12=132 | | 2(x+4.2)=16.2* | | 12=x/4+5 | | 6b-9=9 | | m/3+6=-2 | | 10(a-5)=6(a-3 | | 5(x+2)=2x+7 | | 5s-3=43 | | -14=-6+-4x | | 9+12=-3(3x-7) | | -20-x/4=22 | | 6+2(x-4)=2((x-1) | | 12=1x-0.3x+18 | | 2+x+2x+4=16+10 | | V=1/3x3.14x12^2x19 | | -9x-14=16-4x | | 17-5x=77 | | 2/5(-5+10y)=14 | | 2x+27=5x+36 | | -4m+3(-3m-2)=59 | | -7x-12=58 | | 15-x=-19 | | y=0.1(1+0.23) | | 259+16h=210+18h | | -8x-11=-45 |